The impact of lesson study on primary mathematics teachers’ instructions in Brunei Darussalam - Suhaili, Ade Shahren; Shahrill, Masitah; Khalid, Madihah (2014)

(untitled)
This paper reports a study on the impact of “Lesson Study” on primary mathematics teachers’ instructions in Brunei Darussalam. The purpose was to determine whether Lesson Study had a positive impact on teachers’ instructions. Quantitative data were collected from; checklists from four research lesson classroom observations, and teachers’ questionnaire that was distributed to 28 practitioners and qualitative data were collected from interviews, reflective journals and the study of lesson plans. From the results, four pathways were identified in which teachers’ instructions had indeed improved, 1) Lesson plan development had broadened teachers’ content and pedagogical knowledge; 2) Observation of students’ learning helped teachers to be more conscious and sensitive towards students’ learning needs and difficulties; 3) The development of teachers’ self-confidence, teaching skills, questioning skills and classroom management skills; and 4) Feedbacks from peers and ‘knowledgeable others’ had made them more aware of the weaknesses and strengths on their own teaching.